Value Creations Through Co-Creation and Collaboration Strategy in SMEs Creative Industry - Agus Rahayu; Ayu Krishna Yuliawati; Suwatno Fakhrudin (Faculty of Economics, State University of Jakarta., 2020)
The study focuses on fashion Small Medium Entreprises (SMEs) in Indonesia utilizing strategies and efforts to develop value creations. It is generated by co-creation and collaboration strategy which are supported by market attractiveness and dynamic capabilities. The objectives of this study are to perform analysis on co-creation, collaboration strategy and value creations of SMEs in fashion industry. The research method is descriptive and explanatory survey. The sample size are thirty one SMEs in Bandung and Partial Least Square (PLS) technique was used to test the hypothesis model. The unique findings is co-creation and collaboration strategy have influence on value creations. Market attractiveness or potential profitability be a major input in formulating and implementing both strategies. The phenomena depicted that optimizing market attractiveness and dynamic input capabilities can help SMEs formulate and implement co-creation and collaboration strategy more effectively to create value for customers (value creations). This research gave theoritical recommendation for fashion industry to enhance their value creations process and to develop co-creation and collaborations strategy.